2012
DOI: 10.1371/journal.pone.0036402
|View full text |Cite
|
Sign up to set email alerts
|

Active PI3K Pathway Causes an Invasive Phenotype Which Can Be Reversed or Promoted by Blocking the Pathway at Divergent Nodes

Abstract: The PTEN/PI3K pathway is commonly mutated in cancer and therefore represents an attractive target for therapeutic intervention. To investigate the primary phenotypes mediated by increased pathway signaling in a clean, patient-relevant context, an activating PIK3CA mutation (H1047R) was knocked-in to an endogenous allele of the MCF10A non-tumorigenic human breast epithelial cell line. Introduction of an endogenously mutated PIK3CA allele resulted in a marked epithelial-mesenchymal transition (EMT) and invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 47 publications
(59 reference statements)
4
29
2
Order By: Relevance
“…Although these authors clearly demonstrated that mTORC2 is required to undergo EMT, their study argued against a major role for mTORC1 in this process, because rapamycin did not affect the TGF-b-induced EMT phenotype. However, in agreement with our findings, a pro-EMT effect of mTORC1 inhibition was suggested by a more recent study (26). Using syngenic MCF10A cell lines with an activating mutation in the PIK3CA gene, Wallin and colleagues showed that pharmacologic mTOR inhibition potentiated EMT and the invasive phenotype resulting from activation of the PI3K pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although these authors clearly demonstrated that mTORC2 is required to undergo EMT, their study argued against a major role for mTORC1 in this process, because rapamycin did not affect the TGF-b-induced EMT phenotype. However, in agreement with our findings, a pro-EMT effect of mTORC1 inhibition was suggested by a more recent study (26). Using syngenic MCF10A cell lines with an activating mutation in the PIK3CA gene, Wallin and colleagues showed that pharmacologic mTOR inhibition potentiated EMT and the invasive phenotype resulting from activation of the PI3K pathway.…”
Section: Discussionsupporting
confidence: 92%
“…mTOR stimulation results in the upregulation of metabolism and cell growth, mainly through protein and lipid syntheses (22). Recent reports have suggested a role for mTOR in the EMT process, but with conflicting results (23)(24)(25)(26). According to Gulhati and colleagues, mTORC1 and mTORC2 complexes positively regulate EMT, as well as the motility and metastastic abilities of colorectal cancer cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that the PIK3CA and HER2 + PIK3CA tumors displayed high expression of EMT and stem cell markers and that induction of PIK3CA promoted mammosphere formation. These data are in agreement with in vitro studies that have implicated the PI3K pathway in EMT (31,32) and stem cell maintenance in breast cancer (33)(34)(35). Therefore, the association between PIK3CA mutations and the claudin-low subtype of breast cancer, as well as EMT and stem-like features, suggests that HER2…”
Section: Her2 and Pi3ksupporting
confidence: 91%
“…[65] AKT hyper-activation and PIK3CA knock-in can promote EMT in various human cancers. [61][62][63][64][65][66] The association between EMT and PI3K activation has also been reported in ERα-negative endometrial carcinomas. [67] Twist overexpression has also been correlated with the induction of tumor cell invasion in GBM.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%